Lokakarya Platform Pembelajaran Digital: Google Workspace untuk Pembelajaran di SMP Muhammadiyah 5 Samarinda - Ahmad Fahrijal Pukeng; Presa Taruna Oliver; Fadillah Angreani; Nayla Najwa Adine (JURPIKAT, 2026)
Digital transformation in education has become an inevitable necessity, particularly for managing the learning process more effectively and efficiently. However, not all educational institutions are able to adapt quickly to these changes, especially schools with limited resources and training. One of the target partners in this community service program is SMP Muhammadiyah 5 Samarinda, which still faces challenges in utilizing digital technology. Based on a situational analysis, teachers do not yet have optimal skills in using digital platforms such as Google Classroom. To address this issue, a team of faculty and students from STMIK Widya Cipta Dharma conducted an intensive, practice-based workshop and provided mentoring. The results of the activity demonstrated an increase in teachers’ digital literacy, improved ability to manage learning through Google Classroom, the development of training modules, and increased use of Google Workspace in the learning process, thereby making the quality of learning more effective and structured at the partner school.